University E-voting System Utilizing Blockchain Technology and Zero-Knowledge Proofs - Lim, Aun Xian (2022)
The emergence and popularization of blockchain technology has changed the technosphere in the past decade, improving different sectors with its application. In University Malaysia Pahang’s student council elections, students have raised concerns with regards to providing personal information to potentially compromised devices, the integrity and verifiability of the election and the need to physically attend the voting venue. A blockchain e-voting system addresses these issues by allowing users to access the election using internet connection, does not deal with personal information of the user at all and the blockchain is published after the elections for all to verify. By employing the DSDM framework and the FastAPI python framework, a web-based blockchain voting application has been successfully developed. After receiving user input through UAT, the blockchain e-voting system has been well received by students and has gained positive feedback in regard to its efficiency and effectiveness, along with demonstrating the verifiability a system may provide with the use of blockchain.